BAKAT & Co / Muhammad Abid Kamaruddin ... [et al.] - Kamaruddin, Muhammad Abid; Abdul Shukor, Saidatul Nor Shakirah; Saiful Azmi, Nur Shuhada; Zainal, Nur Shafiqah; Salleh, Aqilah (2021)
This report was written to create a business by using guidelines of Business Model Canvas (BMC). The business that has been created and named as BAKAT & Co, which was founded by a partnership involving 5 people to manage the company. The company can be found at Taman Damansara Aliff, Johor Bahru that produces and sells batik fabrics with a lot of various patterns. Other than that, this report also contains the problem statement and solution to solve it that is faced by BAKAT & Co to sell the batik fabrics nowadays. Furthermore, SWOT analysis is included for BAKAT & Co to identify and plan the business for the present and future which have strengths, weaknesses, opportunity and threat. Next, there is the business proposal for BAKAT & Co to change the business plan by using BMC. First, for value propositions, the best way to take the attention of the targeted market about batik fabrics is exposure and raise awareness of the forgotten tradition, increase the demand for batik, generate sources of income, and the government has enforced a policy requiring public servants to wear batik on Thursdays. Hence, for the customer segment, BAKAT & Co has targeted people who treasure national heritage, the local customer and Malaysian employees. Further, BAKAT & Co uses a few channels to spread the brand awareness which is through social media, the official website and a physical store. Besides, for channel relationships, BAKAT & Co maintain the relationship forged with each of its customers through how to get their customers, how to keep the customers and grow their customers. Additionally, the main revenue streams in BAKAT & Co are from product sales, advertising and outfit rental. BAKAT & Co also operate their business successfully by using key resources. For example, physical resources, financial resources, human resources, and intellectual resources. Moreover, BAKAT & Co also grows by forming collaborative ventures with marketing agencies, expert designers, and suppliers using the key features. Then, in order to reap the company's profits, BAKAT & Co prioritizes the main business activities that have been divided into 4, which are production, problem solving, software tools and platform or network. Last but not least, for the cost structure, BAKAT & Co attaches great importance to the expenses incurred by the company to make sure everything is under control to build a successful company. Therefore, BAKAT & Co uses several measures such as company strategy, cost categories (fixed and variable), and business economics.